The Criticalness Of Surveillance From Jack To Roan In Susan Mihalic’s Dark Horses - Kartiningsih, Rindrah; Hamidah, Galuh Fadhelah Aulia; Pasopati, Rommel Utungga; Siadari, Yoshua Veron Handika Putra; Wijaya, Kusuma (Gudang Jurnal Multidisiplin Ilmu, 2024)
This study aims to examine how the concept of surveillance is carried out by Montgomery in his role as the father figure with authority in the novel Dark Horses by Susan Mihalic in 2021. The researchers use a qualitative method and explorative approach, focusing on contexts and in-depth subjective interpretations. The surveillance is supported by Michel Foucault’s ideas on surveillance, normalization, and disciplinary actions. The analysis looks at how Jack, Roan's father, uses surveillance to control Roan's behavior and enforce normalization and disciplinary actions. This surveillance reflects the father's role as the authoritative figure in the family as reflection of governmentality. In conclusion, the study confirms that Jack's surveillance over Roan proves a father can control the actions and behavior of family members to ensure they follow his rules and desires.